Fintech Lending: Persepsi Diri, Lingkungan Sosial, dan Keputusan Meminjam Mahasiswa - Rizqoh, Ulfatun Ziadatur; Hendaryati, Neni; Azami, Tomi (Jurnal Pendidikan Ekonomi Undiksha, 2025)
Finding out how much influence self-perception and social environment on lending decisions on Fintech Lending applications is the purpose of this study. Using a quantitative approach with an associative correlation research method, the population is active students of the Undergraduate Program (S1) of Pancasakti Tegal University in 2019. Sampling was done using a proportional random sampling technique. The results of the study stated that self-perception had an effect on the decision to borrow with a significance of 0.00 and the magnitude of influence of 28.9%. Meanwhile, the social environment has a positive effect on the decision to borrow with a significance value of 0.00 with a greater effect of 18.9%. In addition, self-perception and social environment have an effect on the decision to borrow with a significance value of 0.00 and a magnitude of influence of 31.8%.  Fintech applications used to borrow money by students are sinjam and exist with use to meet personal needs, lectures and lifestyle fulfillment.